Suomen maalajien ominaispainosta - Heinonen, Reijo (Agricultural and Food Science, 1957)
The specific gravity of Finnish soils is directly correlated with the clay content. This is explained by the uniform mineralogical nature of Finnish soils. The heavy micaceous material is concentrated in the clay fraction. The effect of organic matter on the specific gravity is derived from the multiple regression analysis.